2020
DOI: 10.1038/s41522-020-0119-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term supplementation of celecoxib-shifted butyrate production on a simulated model of the gut microbial ecosystem and ameliorated in vitro inflammation

Abstract: Celecoxib has been effective in the prevention and treatment of chronic inflammatory disorders through inhibition of altered cyclooxygenase-2 (COX-2) pathways. Despite the benefits, continuous administration may increase risk of cardiovascular events. Understanding microbiome-drug-host interactions is fundamental for improving drug disposition and safety responses of colontargeted formulations, but little information is available on the bidirectional interaction between individual microbiomes and celecoxib. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…High-throughput amplicon sequencing of the V3 -V4 hypervariable region (Klindworth et al, 2012) was performed with the Illumina MiSeq platform (LGC Genomics GmbH, Berlin, Germany) and the following primers were used 338f and the 518 r (Øvreås et al, 1997). Bioinformatics and data pre-processing followed a protocol developed in-house (El Hage et al, 2019;Grunert et al, 2019;Hernandez-Sanabria et al, 2020). A generalized linear mixed model was employed to compute the effect of tomato cultivating system and time and the interactions between "tomato cultivating system" and time on each individual genus (El Hage et al, 2019;Grunert et al, 2019;Hernandez-Sanabria et al, 2020).…”
Section: Bacterial Community Structure and Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-throughput amplicon sequencing of the V3 -V4 hypervariable region (Klindworth et al, 2012) was performed with the Illumina MiSeq platform (LGC Genomics GmbH, Berlin, Germany) and the following primers were used 338f and the 518 r (Øvreås et al, 1997). Bioinformatics and data pre-processing followed a protocol developed in-house (El Hage et al, 2019;Grunert et al, 2019;Hernandez-Sanabria et al, 2020). A generalized linear mixed model was employed to compute the effect of tomato cultivating system and time and the interactions between "tomato cultivating system" and time on each individual genus (El Hage et al, 2019;Grunert et al, 2019;Hernandez-Sanabria et al, 2020).…”
Section: Bacterial Community Structure and Compositionmentioning
confidence: 99%
“…Bioinformatics and data pre-processing followed a protocol developed in-house (El Hage et al, 2019;Grunert et al, 2019;Hernandez-Sanabria et al, 2020). A generalized linear mixed model was employed to compute the effect of tomato cultivating system and time and the interactions between "tomato cultivating system" and time on each individual genus (El Hage et al, 2019;Grunert et al, 2019;Hernandez-Sanabria et al, 2020). Differences among library size sample were accounted for with the offset option in proc GLIMMIX in SAS (Paschold et al, 2012;El Hage et al, 2019).…”
Section: Bacterial Community Structure and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this small study, the inter-individual variability in response to celecoxib could have masked the effect of this drug on the diversity of the gut microbiota. On this note, a recent study reported that without altering the composition of the microbiota, celecoxib can decrease microbial butyrate production in a human intestinal microbiota ecosystem model and also diminish markers of inflammation like IL-8 and CXCL16 in intestinal cells in vitro (Hernandez-Sanabria et al, 2020).…”
Section: Human Studiesmentioning
confidence: 99%
“…This implies that the relation between plasma concentrations and efficacy has a low predictive value. For this reason, investigating microbiome-drug-host interactions towards improving ADME and safety responses of intestinal targets is fundamental [12].…”
Section: Introduction mentioning
confidence: 99%